Expression pattern and function of eIFE4 isoforms in planarian adult stem cells - Tuqan, Duniazad F (2011)
The eukaryotic translation initiation factor 4E (eIF4E) is central to translation initiation in eukaryotic cells. Recent studies revealed that there are multiple isoforms of eIF4E present in different species, some of which were found to have specific functions other than translation initiation. Furthermore, some were found to be expressed during specific developmental stages and/or in specialized tissue types. Multiple isoforms of elF4E have been found in several model organisms. For example, five eIF4Es were found in Caenorhabditis elegans, three in mammals and sea urchins, two in zebrafish and eight in Drosophila (Henderson et al., 2009). Among these species, stem cell specific isoforms were found in mouse, C. elegans, and Drosophila (Amiri et al., 2001). None of the eIF4E isoforms have yet been investigated in planarians which is an ideal model organism for studying stem cell biology in vivo.